Biofunctional properties and production of peptides from Fermented cheddar cheese whey fractions using Limosilactobacillus fermentum - Bhagyashree Das, Kunal Gawai, Kaushik Das, Hiral Kumari Patel; Subrota Hati (Indian Journal of Dairy Science, 2026)
This investigation was conducted to analyse the antioxidant activity, proteolytic activity and ability of short-chain fatty acids (SCFAs) production from fermented cheddar cheese whey fractions inoculated with Limosilactobacillus fermentum, MF951096 (M4) @ 2.5% when incubated at 37°C for 48 h. Ultrafiltration membranes with appropriate molecular weight thresholds were used to isolate low-molecular-weight peptides from fermented whey, including the 3 kDa permeate, 10 kDa permeate, and retentate fractions. In acidity and pH profile, there was no significant difference observed. Significantly higher peptide content (7.84mg/mL) and antioxidant activity (65.81%) were observed in the 10 kDa retentate fraction; however, no significant difference in lactic count was observed among the fractions. Also we characterized the peptide fractions by analysing their chromatographic peaks using RP-HPLC. The 10 kDa retentate fraction produced the most SCFA i.e. 46.68 μg/mL acetic acid, 21.59 μg/mL propionic acid, and 5.27 μg/mL butyric acid, respectively. From this investigation, we concluded that the conversion of dairy waste into bioactive molecules presents a novel approach with conceivable applications in the dairy, food and pharmaceutical sector.